Comparison of Hill‐radial basis function, Barrett Universal and current third generation formulas for the calculation of intraocular lens power during cataract surgery. (31st August 2017) - Roberts, Timothy V; Hodge, Chris; Sutton, Gerard; Lawless, Michael; ,
Abstract: Importance: This study represents a novel comparison of recently introduced intraocular lens power calculation formulas. Background: To compare current new generation formulas for calculating the intraocular lens power for a standard cohort of patients undergoing cataract and lens replacement surgery in a private group practice in Australia. Design: Retrospective case series comparison. Participants: Postoperative results from 400 consecutive patients undergoing implantation of an SN60WF intraocular lens post cataract removal by 12 surgeons were used. Methods: Refractive outcomes were compared with expected targets to determine the predicted refractive outcomes using the Hill‐radial basis function, Barrett Universal II and readily available third or fourth generation intraocular lens power calculation formulas. Main Outcome Measure: Mean absolute predicted error. Results: The mean absolute predicted difference ranged from 0.30 to 0.34 D. There was no overall significant difference in the predicted difference or variance between formulas. All formulas achieved greater than 78.3% of eyes within ±0.5 D of intended refraction. The Hill‐radial basis function and Barrett formulas provided the lowest mean numerical error compared with existing formulas in short and long eyes, respectively. The Barrett Universal II formula had the lowest percentage of refractive surprises (>1 D from predicted error) across all axial lengths. Conclusions and Relevance: Acceptable outcomes can be achieved with optical biometry, consistent surgical technique and use of current intraocular lens power calculation formulas. The Barrett Universal II formula may provide the lowest risk of refractive surprise compared with other intraocular lens power calculation formulas.